Impaired cardiac structure and systolic function in athletes using supra-physiological doses of anabolic androgenic steroids - Hammoud, Sabah; van den Bemt, Bart J.F.; Jaber, Ayman; Kurdi, Mazen (Journal of science and medicine in sport, 2023)
Athletes are increasingly using supra-physiological doses of anabolic androgenic steroids without weighing health side effects. This study aims to conjointly evaluate the effect of supraphysiological doses of anabolic androgenic steroids on global cardiovascular structure and functional capacity. Cross-sectional study. 92 males enrolled in the study, including 18 sedentary subjects, 26 anabolic androgenic steroid non-user athletes, and 48 anabolic androgenic steroid-user athletes. Two-dimensional echocardiography was done to evaluate the cardiovascular structure and function. Anabolic androgenic steroid-users presented increased cardiac remodeling of the left ventricle and left atrium compared to control groups (p < 0.001). Anabolic androgenic steroid-users showed increased left ventricular mass/body surface area versus control groups (p < 0.001), with 28 steroid-users (58.3 %) having cardiac remodeling, which is more than control groups (p < 0.001). Anabolic androgenic steroid-users presented lower diastolic function (E and E/A) compared to non-users (p = 0.003 and <0.001, respectively). Ejection fraction was decreased among anabolic androgenic steroid-users versus the sedentary group only (p = 0.020), while anabolic androgenic steroid-users presented reduced global longitudinal strain of 15.43 % compared to both control groups (p < 0.001). Moreover, anabolic androgenic steroid-users experienced more tricuspid valve regurgitation (p = 0.001). Anabolic androgenic steroid consumption is associated with global cardiac remodeling with increased dimensions of the left ventricle, and atrium. Anabolic androgenic steroid-users present left ventricular hypertrophy with reduced subclinical systolic function. Moreover, anabolic androgenic steroid consumption is correlated with valve regurgitation and dilation of the sino-tubular junction.